Exploring metaverse online platform “Gather.Town” for collaborative learning activities to improve participants’ engagement in adolescent health workshop intervention - Velies, Dyana Safitri; Jocelyn, Jocelyn; Wibowo, Johan; Sungono, Veli (Faculty of Medicine, Public Health, and Nursing, Universitas Gadjah Mada, 2025)
Introduction: Health-related behavior in adolescents gives significant impact on their future health and the next generation. Some interventions toward adolescents’ health-related behaviors have resulted ineffectively, owing to status and respect sensitivity in adolescents’ uniqueness. Covid-19 pandemic caused restrictions to face-to-face meetings and educational activities. The